Effect of mechanical properties with addition of graphene nano-platelets in Cu/ GNPs composite- green part - Muhammad Omar Abdul Rashid,; Norhamidi Muhamad,; Abu Bakar Sulong,; Nor Nabilla Kadiman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Graphene is one of the best reinforcement materials but have a strong tendency to agglomerate and will affect the final properties of the composite. Effect of mechanical properties with addition of Graphene Nano-platelets (GNPs) in copper through powder injection molding (PIM) process was investigated. 2 feedstocks was prepared, one is Cu 100% and Cu/0.5 vol.% GNPs. Both feedstocks use same powder loading, 62% powder and 38% binder and the binder system used for this study consist of polyethylene glycol (PEG), polymethyl methacrylate (PMMA) and stearic acid (SA). The feedstocks were sonicated, and ball milled using the same parameters and then continue with until injection process. The produced green part strength and density were tested. The main reason to for density testing is to determine either addition of GNPs will affect the composite density The average green density for Cu 100% is 5.835 g/cm3, which is 99.84 % from the theoretical density. Meanwhile for Cu/GNps 0.5%, the average density is 5.874 g/cm3, which is 99.91 % from the theoretical density. For the green strength, the average maximum flexural strength for Cu 100% is 15.29 MPa and 14.32 MPa for Cu/0.5 vol.% GNPs. Even though the density of Cu/GNPs composites decrease with addition of 0.5 vol% GNPs but both sample strength indicates good mechanical properties and suitable for debinding and sintering process.